Knowledge spillovers along the sustainable supply chain of China's listed companies: The role of long-term orientation - Lifeng Chen; Qitaisong Shen; Xiaolan Yu; Xiaohui Chen (Journal of Innovation & Knowledge (JIK), 2024)
A new industrial development paradigm, the Fifth Industrial Revolution or 'Industry 5.0' is expected to humanise green technological innovation (GTI), social resilience, and sustainable development of industrial ecosystems. Emphasising the supplier-customer interaction, 'Industry 5.0' is technological revolution, which is a value-driven initiative that drives knowledge spillovers along the sustainable supply chain (SSC). In this context, enterprises are incorporating more GTI activities into their partners' SSC strategies. This study employs samples of China's A-share listed companies covering the period from 2010 to 2021 to examine the spillover effects between customers' GTI and suppliers total factor productivity (TFP). Both GTI and TFP indicators are important representations of 'Industry 5.0', with our major concerning on the enhancement of supplier's long-term orientation (LTO). We calculated TFP by the Olley-Pakes and Levinsohn-Petrin methods, dividing GTI indicators into three levels: substantial green technological innovation (SGTI), non-substantial green technological innovation (NGTI), and overall green technological innovation (OGTI). Our empirical results show that 1) Customer's GTI contributes to supplier's TFP, and supplier's LTO including environmental, social & governance (ESG) performance, and R&D input can strengthen this beneficial link; 2) customer's NGTI represents a significant differentiation in comparison with SGTI, where R&D investment weakens the positive relationship between customer's NGTI and supplier's TFP; 3) heterogeneity analysis indicates that the spillovers of customer's GTI on supplier's TFP are more pronounced among state-owned enterprises, high-tech enterprises, and non-polluting enterprises. Notably, the connectedness demonstrates dynamic patterns through 2SLS and GMM regressions, highlighting the importance of enterprises' SSC and LTO being the shock transmitters to their TFP. Our study is prone to benefit lawmakers, regulators, and firm executives responsible for analysing and assessing the SSC, providing more policy implications with future prospects for sustainable transformation in the upcoming 'Industry 5.0' era.
Keywords: G18; G30; O30; O32; 650; Green technological innovation; Industry 5.0; Long-term orientation; Sustainable supply chain; Total factor productivity